Third Edition of the Code of Virginia: Including Legislation to January 1, 1874 Page 802-803, tit. 29, ch. 99, § 5 (1873) - (:unkn) unknown (My University, 1865)
If any person shall hunt, shoot, fowl or range with or without dogs, on the lands of another, without the consent of the owner or tenant of such lands, or shoot along any public road, or in the streets of any town or village, in any of the counties of this commonwealth, on the lands comprehended in the survey of any proprietor, he shall be deemed guilty of a trespass, and shall be fined for each offense five dollars
Keywords: HUNTING REGULATION